RBM10 regulates centriole duplication in HepG2 cells by ectopically assembling PLK4‐STIL complexes in the nucleus. (20th January 2020) - Kunimoto, Hiroyuki; Inoue, Akira; Kojima, Hirotada; Yang, Junhao; Zhao, Hong; Tsuruta, Daisuke; Nakajima, Koichi
Abstract: RNA‐binding motif protein 10 (RBM10) primarily regulates alternative splicing of certain genes. Loss‐of‐function mutations in RBM10 have been frequently reported in patients with various cancers. However, how RBM10 levels affect cell proliferation and tumorigenesis remains unknown. To elucidate the role of RBM10 in cell proliferation, we established HepG2‐RBM10 knockout cell lines and derivative doxycycline‐inducible RBM10‐expressing cells. RBM10 over‐expression caused growth arrest in the M phase with a monopolar spindle because of impaired centriole duplication. Two RBM10 splicing mutants, one with F345A/F347A and the other with only the C‐terminal half (401–930), were sufficient to cause growth arrest, whereas an RBM10 mutant with cytoplasmic localization forced by an NES did not show growth arrest. RBM10 over‐expression induced the formation of many large nuclear domains containing RBM10, PLK4, STIL and SAS6, which are the regulatory proteins involved in centriole duplication. Consistently, the centrioles in the RBM10‐over‐expressing HepG2 cells lost PLK4 and STIL, accounting for the unsuccessful centriole duplication. In contrast, RBM10 depletion resulted in elevated levels of cytoplasmic PLK4 with a concomitant increase in the number of centrioles in HepG2 cells but not in A549 cells. Thus, nuclear RBM10 regulates normal chromosomal division in a cell‐type‐specific manner, independent of alternative RNA splicing. Abstract : Over‐expression of RBM10 causes growth arrest in the M phase with a monopolar spindle because of impaired centriole duplication through ectopically assembling PLK4‐STIL complexes in the RBM10‐containing nuclear domains, leading to depletion of PLK4 for centriole duplication. Interestingly, RBM10 depletion resulted in elevated levels of cytoplasmic PLK4 with a concomitant increase in the number of centrioles in HepG2 cells but not in A549 cells.